THE EFFECT OF STRESS RATIO ON THE FATIGUE THRESHOLD CONDITION OF PHYSICALLY SMALL CRACKS - Lal D.N. (My University, 2025)
An approach is proposed to predict the intrinsic threshold of physically small cracks without invoking crack closure considerations. The basic assumption invoked is that a ΔK representation is valid for short cracks, hence the lower‐bound threshold value, ΔK0(s)(min) for short cracks can be numerically equated with the lower‐bound threshold value of long cracks, ΔK*0(l)(min), s of the same material. Several experimental observations provide a basis for this rationalization. The approach allows a quantitative prediction of stress ratio and crack length dependence of ΔK0(S) which provides good agreement with experimental data for several low‐strength steels and aluminium alloys. This alternative procedure may be found useful in design applications. Copyright © 1993, Wiley Blackwell. All rights reserved